Human chorionic gonadotropin and GnRH effects on pregnancy survival in pregnant cows and resynchronized pregnancy rates - Buttery, B.S.; Burns, M.G.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Experiments have shown human chorionic gonadotropin (hCG) to be more effective than gondadotropin releasing hormone (GnRH) as a means to ovulate follicles. Experiment 1 determined the effects of replacing the first injection of GnRH (day 7) with hCG or saline in a Resynch-Ovsynch protocol on pregnancy rates in cows subsequently diagnosed not pregnant and pregnancy survival in cows subsequently diagnosed pregnant (day 0). A second study determined the ovulation potential of hCG compared with GnRH and saline (Exp. 2). In Exp. 1, cows in 4 herds were assigned randomly based on lactation number, number of previous AI, and last test-day milk yield to treatments of 1,000 IU of hCG, 100 μg of GnRH, or left as untreated controls 7 days before pregnancy diagnosis. Cows found not pregnant were given PGF2α (day 0), then inseminated 72 hours later, concurrent with a GnRH injection (3 herds) or given GnRH 16 to 24 hours before AI at 72 hours (1 herd). Timed AI pregnancy rates tended (P = 0.08) to be reduced by saline (12.9%; n = 505) compared with GnRH (17.9%; n = 703) but not hCG (16.5%; n = 541). Among pregnant cows treated, pregnancy survival 4 to 9 weeks after initial pregnancy diagnosis differed among herds (P < 0.001); but in 1 herd, GnRH reduced pregnancy survival, whereas hCG seemed to increase survival compared with control. Only small differences were detected in the other 3 herds, except for a slight negative effect of hCG compared with control in 1 herd. Ovarian structures were monitored in herd 1 by using transrectal ultrasonography 0 and 7 days after treatment with hCG, GnRH, or saline (Exp. 2). A tendency for a treatment × pregnancy status interaction (P = 0.07) was detected. Incidences of ovulation in nonpregnant cows were: hCG (51.6%; n = 126), GnRH (46.1%; n = 102), and control (28.1%; n = 96), whereas those in pregnant cows were: hCG (59.3%; n = 59), GnRH (24.5%; n = 49), and saline (6.9%; n = 58). We concluded that: 1) initiating a Resynch-Ovsynch protocol 7 days before pregnancy diagnosis with saline reduced timed AI pregnancy rates (Exp. 1); 2) in pregnant cows treated with GnRH, pregnancy survival was slightly reduced in 1 of 4 herds (Exp. 1); and 3) incidence of new corpus luteum (CL) was greater after hCG than GnRH in pregnant cows but not in nonpregnant cows (Exp. 2).
Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy; hCG; GnRH; Pregnancy rates